Ethnic Boundary among Multi-Ethnic Primary School Pupils in Malaysia: Role of Teachers and Administrators - Ahmad, Yasmin; Yusof, Najeemah M. (International Journal of Independent Research Studies, 2013)
This paper is a study of ethnic boundary among primary pupils in Penang Malaysia. It discussed the roles of teachers and school administrators in narrowing the visual circle of socio-ethnical gaps. The study investigates whether the differences between mono-ethnic and multi-ethnic schools environment would have an impact on the roles of teachers and administrators in narrowing the socio-ethnic boundary among school pupils. The research study was carried out in Penang involving 12 primary schools. The sample size of pupils for the study was 600. Structured questionnaire is used to collect the responses. The result of the study showed that teachers and administrators play an important role in narrowing the ethnic boundary among multi-ethnic pupils. The narrowing of ethnic boundaries (differences) is vital tool for social integration. It is considered as a pre-requisite for peaceful coexistence which is an integral part of socio-ethnic and National development in a pluralistic society such as Malaysia.